Whole-Body CT Trauma Imaging with Adapted and Optimized CT Angiography of the Craniocervical Vessels: Do We Need an Extra Screening Examination? - Langner, S.; Fleck, S.; Kirsch, M.; Petrik, M.; Hosten, N. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Blunt carotid and vertebral artery injury (BCVI) is rare but potentially devastating. The objective of our study was to prospectively evaluate the usefulness of a dedicated and optimized CT angiography (CTA) protocol of the craniocervical vessels as part of a whole-body CT work-up of patients with multiple trauma in a population of patients with blunt trauma.MATERIAL AND METHODS: From February 2006 to July 2007, a total of 368 consecutive patients with trauma were evaluated. All examinations were performed on a 16-row multisection CT (MSCT) scanner. CTA was performed from the level of the T2 vertebra to the roof of the lateral ventricles with 40 mL of iodinated contrast agent. Images were reconstructed with use of the angiography and bone window settings to evaluate vessels and bones.RESULTS: Of all eligible patients imaged, 100 had injuries to the head and neck including 35 skull base fractures (9.5%), 24 maxillofacial (6.5%), and 11 cervical spine fractures (3%). CTA was diagnostic in all patients. BCVI was diagnosed in 6 cases (6 lesions of the internal carotid artery, 3 lesions of the vertebral artery); among them were 2 who did not meet the screening criteria. No patient with negative results on CTA subsequently had development of neurologic deficits suspicious for BCVI.CONCLUSION: This study confirms that optimized craniocervical CTA can be easily integrated into a whole-body CT protocol for patients with multiple trauma. No additional screening technique is necessary to identify clinically relevant vascular injuries. Earlier recognition enables earlier treatment and may decrease mortality and morbidity rates of these rare but potentially devastating injuries.